Add parser support for sumof with a nested expression.
For example:
<sumof ref="mylist1">
<fieldref>bar</fieldref>
</sumof>
The nested expression is added as the "rhs"-field of the
expression.object.
Signed-off-by: Christian Linhart <chris@demorecorder.com>
Reviewed-by: Ran Benita <ran234@gmail.com>
Message-ID: <
545627E1.8070302@DemoRecorder.com>
Patch-Thread-Subject: [Xcb] [PATCHSET] ListInputDevices revision 2
Patch-Set: ListInputDevices
Patch-Number: proto 4/8
Patch-Version: V1
elif elt.tag == 'sumof':
self.op = 'sumof'
self.lenfield_name = elt.get('ref')
+ subexpressions = list(elt)
+ if len(subexpressions) > 0:
+ # sumof with a nested expression which is to be evaluated
+ # for each list-element in the context of that list-element.
+ # sumof then returns the sum of the results of these evaluations
+ self.rhs = Expression(subexpressions[0], parent)
else:
# Notreached